Analisis Level Kinerja Practitioner Melalui Aktivitas Belajar Siswa - Eric Dwi Putra; Indah Rahayu Panglipur (Jurnal Pendidikan Matematika:Judika Education, 2019)
The purpose of the study, determine the level of performance of practitioners through student learning activities. The level of student practitioner performance is seen when solving mathematical problems (story problems) sub-topics of numbers. The research method used is quantitative descriptive. The analysis technique uses validity test and source triangulation. In this study the subjects of class VII students were taken as many as 6 people. Retrieval of data using observations and questions (problems). Data were observed using an observation sheet instrument, while questions with realistic media. The results of the study, the validation of the instrument on the observation sheet using the Va value for the test questions obtained 2.9 results thus the instrument is said to be valid. Based on the results of observations ST satisfies all activities well but in activities related to courage still can not be said to always be brave in responding and asking questions / opinions expressly, SS fulfills 3 out of 6 student activities well. These results are the same for the 2 subjects taken. SR fulfills 5 out of 6 student activities well. These results are the same for the 2 subjects taken. Conclusions, the Practitioner student's level of performance has different levels of fulfillment of critical standards through student learning activities. Students with high ability category (ST) can meet all critical standard indicators while students with medium (SS) and low (SR) ability categories cannot fulfill. Key Words: Performance Level Practitioners, Learning Activities